Evaluating the Effect of Body Mass Index on Procalcitonin Level in Patients with Pneumonia: A Retrospective Cross-Sectional Study - Mohammad Z. Khrais; J. Curran Henson; Jake Smith; Nikhil Meena (Advances in Respiratory Medicine)
Procalcitonin (PCT) is commonly used to evaluate the etiology and severity of pneumonia. PCT has been shown to be elevated at baseline in patients with obesity. The aim of this study is to determine if body mass index (BMI) has an influence on admission PCT level in patients admitted to the hospital with a diagnosis of pneumonia. We conducted a retrospective cohort study that encompassed patient visits to a tertiary care center from 2014 until September 2023. A total of 18,652 patients presented to the emergency department with a diagnosis of pneumonia. A total of 3659 were admitted to the floor, and 2246 were admitted to the MICU. Patients were grouped based on admission BMI into five categories. The Kruskal–Wallis test performed on patients admitted to the floor revealed a statistically significant difference in PCT levels among groups of different BMIs (H = 34.97, df = 4, p < 0.001). In patients admitted to the MICU, the Kruskal–Wallis test revealed a significant difference in PCT levels among groups of different BMIs (H = 32.92, df = 4, p < 0.001). BMI has a statistically significant effect on PCT in patients admitted to the hospital with pneumonia. Patients with higher BMI may exhibit less robust PCT levels, which may impact management decisions.